KEBIJAKAN PEMBINAAN GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU TAHUN 2017 - Nur Adila Arazi; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Almost all big cities in Indonesia are jammed with homeless people and beggars, including Pekanbaru City. To overcome the problems of homelessness and beggars, it is necessary to intervene by the Regional Government, especially Pekanbaru City and the Pekanbaru City Social Service to handle homeless people and beggars, one of which is done by formulating Pekanbaru City Government Policy, namely by making Pekanbaru City Regional Regulation Number 12 of 2008 concerning Social Order. The reason for the issuance of the Pekanbaru City Regional Regulation No. 12 of 2008 is to address welfare problems in Pekanbaru City, which in this study will focus on fostering homeless people and beggars.Whatever the purpose of this research is to find out how the policies for the development of the homeless and beggars in 2017 and the inhibiting factors for the development policies of the homeless and beggars. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.Based on the results of research and findings in the field regarding the policy of fostering homeless people and beggars in Pekanbaru City in 2017, it has not been running optimally which has led to the return of homeless people and beggars after receiving guidance. The impact of the coaching policy carried out by the Pekanbaru City Social Service has not yet been felt in reducing the number of homeless and beggars because the training carried out by the Pekanbaru City Social Service only provides mental coaching for a short time and in skills training activities it no longer runs. Inhibiting factors in carrying out coaching homeless people and beggars, both from internal and external factors. From internal factors, namely: Limited budget, absence of social rehabilitation centers belonging to the Regional Government. External factors, namely there are still many people who give money to homeless people and beggars, there is no cooperation from the private sector or business entities to carry out special skills training for homeless and beggars.Keywords: Policy, Development, Homeless, Beggars